Spermatozoon ultrastructure in two monorchiid digeneans - Quilichini, Yann; Bakhoum, Abdoulaye J.S.; Justine, Jean-Lou; Bray, Rodney A.; Bâ, Cheikh T.; Marchand, Bernard (PeerJ, 2016)
Spermatological characteristics of species from two monorchiid genera, Opisthomonorchis and Paramonorcheides, have been investigated, for the first time, by means of transmission electron microscopy. The ultrastructural study reveals that the mature spermatozoon of Opisthomonorchis dinema and Paramonorcheides selaris share several characters such as the presence of two axonemes of different lengths showing the 9+“1” pattern of the Trepaxonemata, a nucleus, two mitochondria, two bundles of parallel cortical microtubules, external ornamentation of the plasma membrane, spine-like bodies, granules of glycogen and similar morphologies of the anterior and posterior extremities. The slight differences between the male gamete of O. dinema and P. selaris are the length of the first axoneme and the position of the second mitochondrion. This study also elucidates the general morphology of the spermatozoon in all monorchiid species described so far, which corresponds to a unique spermatozoon type. Other interesting finds concern the spermatological similarities between monorchiid spermatozoa and the mature spermatozoon reported in the apocreadiid Neoapocreadium chabaudi. These similarities allow us to suggest a close phylogenetical relationship between the Monorchiidae and the Apocreadiidae, although more studies are needed, especially in the unexplored taxa.
Keywords: Sperm; Ultrastructure; Digenea; Monorchiidae; Opisthomonorchis; Paramonorcheides; TEM